Classic Islamic Education Heritage in Halaqah and Munazharah - Asmar Yamin Dalimunthe (Institut Agama Islam Negeri Padangsidimpuan, 2020)
The halaqah method is still used by Muslims Society today, especially when studying in mosques and the learning system during the ta`aruf period in Islamic Universities. Meanwhile munazarah, which has begun to be abandoned, has returned to appear in the debate system of presidential election, although not entirely the same. This paper uses historical and philosophical methods. Both of these methods are relevant to the problem. Halaqah and munazarah are well-established and attractive education systems. Halaqah as a learning system is seen from the seated position of the teacher and students who mingle, while munazarah is a stage for a sportive intelectual selection. Halaqah in the classical education system is no longer used today, but the learning system in S2 and S3 is precisely what is used. Munazarah needs to be activated now to test one.